Implementation of advanced techniques in production and manufacturing sectors through support vector machine algorithm with embedded system - Rayner Alfred; Narender Chinthamu; T. Jayanthy; Elangovan Muniyandy; Tarun Kumar Dhiman; Nimmy John T. (Elsevier B.V., 2024)
Our study set out to explore the integration of digital twins into manufacturing and production sectors with the aim of enhancing sustainability and operational efficiency. Employing a structured methodology, we utilized advanced 3D modeling techniques to create virtual representations of physical environments and products, forming the basis of our digital twin ecosystem. Through virtual product implementation, we simulated product behavior and performance, facilitating comprehensive testing and analysis before physical manufacturing. Leveraging artificial intelligence, particularly Support Vector Machine (SVM) optimization, we conducted performance analysis by processing data from interconnected sources, including social media platforms, to optimize digital transformation processes. Our results indicate that digital twins significantly enhance operational efficiency by detecting inefficiencies early, reducing production costs, and expediting time-to-market. Moreover, they contribute to sustainability efforts by minimizing resource wastage and environmental impact during manufacturing processes. The adoption of digital twins also fosters a culture of innovation and continuous improvement, enabling technological advancements and adaptability in corporate and industrial settings. In conclusion, our findings underscore the transformative potential of digital twins in driving positive change and optimizing industrial processes.